Assessment of Compound Flood Hazards in the Rijeka City Center Due to the Combined Action of the Sea and the River (Proceedings of Faculty of Civil Engineering, 2023)
In this paper, an assessment of the compound flood hazards in the city center of Rijeka due to the combined actions of the coastal and river flood sources was carried out, and hazard maps for the said area were prepared. Maps were created on a larger scale, taking into account various sources of flooding, and they show that the city of Rijeka has a high level of flood hazard, especially along the coastline and around the Rječina river where the highest flow velocities and water depths can be expected.
Keywords: flood hazard maps; compound floods; city of Rijeka; assessment of flood hazards; coastal flooding; fluvial flooding